Pemanfaatan Lengkuas (Alpinia galanga L. Swartz) Untuk Mengawetkan Ikan Pindang Tongkol (Euthynnus pelamis L.) - Atmodjo, Kianto; Aida, Yuniarti; Mursyanti, Mursyanti (Universitas Atma Jaya Yogyakarta, 2003)
The objective of this research was to prove that galangale rhizome (Alpinia galanga L. Swartz) can be used to preserved â€œpindangâ€ tuna fish (Euthynnus pelamis L.). The fish were cooked by galangale rhizome solution (the concentration were 0, 50, 100, 150, 200 mg/l b/v) for15 minutes. Then, the fish were stored in box, three fishes /box, and stored at room temperature for 6 days. Every day, The quality of fish were measured as colour, rubberness, taste, odor, total of bacteria and fungi. The result showed that there were decreased of the fish quality, spoilaged, and many fungi and bacteri growth after two days, and the level of spoilage of fish was influenced the increasing of galangale rhizome concentration. It concluded that the galangale rhizome can not use as â€œpindangâ€ tuna fish preservative.